EVALUASI PELAKSANAAN PROGRAM OPEN DEFECATION FREE (ODF) DI WILAYAH KOTA SURABAYA - Intan Putri Rachmawati; Khambali .; Hadi Suryono (Poltekkes Kemenkes Surabaya, 2020)
ABSTRACT The city of Surabaya has 60 villages that have been verified as Open Defecation Free (ODF) from 154 villages with 867,009 households, and there are 94 villages that are still defecated around 14,900 households. In the implementation of the ODF program there are several problems so that indicators of the success of the ODF program are not achieved. The purpose of this study is to evaluate the implementation of the ODF program in the Surabaya City Region.This type of research is a survey using an explanatory squared mixed metods design. The research sample was 65 people, namely health workers, community leaders and the community. The variables in this study are the causal factors and the implementation of the ODF program. Data collection is done by questionnaires and interviews. Data analysis used inferential statistical analysis with Spearman rank correlation test.The results of the study indicate that the implementation of the ODF program is not in accordance with the plan and lacks supervision of the target. Based on hypothesis testing using the Spearman rank test, that all independent variables are significantly associated with the implementation of ODF programs. The dominant factor in implementing the ODF program is education because the correlation value is 0.769 with a strong level of relationship.The implementation of the ODF program is in the less category so that it is necessary to periodically monitor targets and technical guidance activities related to the implementation of the ODF program to increase knowledge, the role of health workers and the role of community leaders, as well as further research with representative samples.Keywords: Implementation, Open Defecation Free (ODF)